Bioactive Fibers: Hydrogel Templates for Rapid Manufacturing of Bioactive Fibers and 3D Constructs (Adv. Healthcare Mater. 14/2015). Issue 14 (7th October 2015) - Tamayol, Ali; Najafabadi, Alireza Hassani; Aliakbarian, Bahar; Arab‐Tehrany, Elmira; Akbari, Mohsen; Annabi, Nasim; Juncker, David; Khademhosseini, Ali
Abstract : Hybrid hydrogel fibers were fabricated using hydrogel templates. On page 2146, D. Juncker, A. Khademhosseini, and co‐workers show how these fibers containing different fluorescent microbeads have been assembled using textile processes, such as braiding and weaving, to create complex 3D patterns for bioengineering applications. The fabricated constructs with clinically relevant dimensions are mechanically stable.